2014
DOI: 10.5194/hess-18-2325-2014
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the human impact on water resources: a critical review of the water footprint concept

Abstract: Abstract. The water footprint is a consumption-based indicator of water use, referring to the total volume of freshwater used directly and indirectly by a nation or a company, or in the provision of a product or service. Despite widespread enthusiasm for the development and use of water footprints, some concerns have been raised about the concept and its usefulness. A variety of methodologies have been developed for water footprinting which differ with respect to how they deal with different forms of water use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 115 publications
1
55
0
2
Order By: Relevance
“…Large-scale models also showed that promoting international trade can be a strong adaptation option for controlling regional demand, in which water-limited regions can import water-expensive products from other areas (e.g., Hanasaki et al, 2010;Konar et al, 2013). Assessment of trade scenarios and water footprinting, however, needs detailed tracking of the water cycle (see Chenoweth et al, 2014) and is highly dependent on how reasonable the human demands and production, as well as water availability and water allocation, are described in time and space. Such a level of accuracy is currently not available and therefore the assessments remain widely uncertain.…”
Section: Offline Representationmentioning
confidence: 99%
“…Large-scale models also showed that promoting international trade can be a strong adaptation option for controlling regional demand, in which water-limited regions can import water-expensive products from other areas (e.g., Hanasaki et al, 2010;Konar et al, 2013). Assessment of trade scenarios and water footprinting, however, needs detailed tracking of the water cycle (see Chenoweth et al, 2014) and is highly dependent on how reasonable the human demands and production, as well as water availability and water allocation, are described in time and space. Such a level of accuracy is currently not available and therefore the assessments remain widely uncertain.…”
Section: Offline Representationmentioning
confidence: 99%
“…Methodologies employed for WF analysis can generally be separated into bottom-up (product level approaches) and top-down (sector level approaches) [60,61]. As a number of reviews have been done on general WF methods (see, e.g., [60][61][62][63]), we highlight three main methodologies which have been used for regional or urban studies: (1) Water Footprint Assessment (WFA) which tends to be employed at the product/commodity level; (2) environmentally extended input-output (EEIO) which uses economic IO tables and thus considers sector level data; and (3) life cycle assessment (LCA) which relies heavily on standardization and databases to estimate the environmental, including water, and health impacts of products along their full life. Hybrid approaches of these methods have also been utilized to integrate scales and available datasets.…”
Section: Methodologies For Water Footprint Analysismentioning
confidence: 99%
“…Applied to commodities, the water footprint indicator also has the potential to empower consumers by providing them with information on the way their choices affect water security globally [12]. However, some authors argue that water footprints do not provide sufficient information on the opportunity cost of water, so it cannot be used as a stand-alone instrument to assess the environmental impacts of water use, unlike the carbon footprint; and it is too aggregated to inform consumer choices [13,14]. Concerns have also been raised about the wide range of different methodological approaches to assess water footprints [14].…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Corporate engagement in water footprint accounting is a useful way to encourage companies to comprehensively take account of their water consumption in their supply chain and to make their environmental impact more transparent, although most of the studies developed so far do not make use of their own spatially-and temporally-explicit water footprint values [14]. It has been recognized that "the value of water footprint is more in its components than in the total sum" [27].…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation